2006
DOI: 10.2215/cjn.01741105
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Analysis of Cellular Infiltrate of Renal Allograft Biopsies in Patients with Acute Rejection after Induction with Alemtuzumab (Campath-1H)

Abstract: Alemtuzumab is a humanized anti-CD52 mAb that has emerged as a safe and effective lymphocyte-depleting agent for induction therapy in renal transplantation. Recent reports have suggested that acute cellular rejection (ACR) of renal allografts in patients who receive alemtuzumab induction may be mediated by an atypical population of monocytes and not through "classical" T cell-dependent pathways of allorecognition. However, more recently, T cells with memory phenotype have been described in renal biopsies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…In renal allografts, episodes of rejection are characterized by recruitment of activated leukocytes into the transplant (17,18,29). This is an integral part of the basic concept of the Banff classification, a commonly used score of renal rejection (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In renal allografts, episodes of rejection are characterized by recruitment of activated leukocytes into the transplant (17,18,29). This is an integral part of the basic concept of the Banff classification, a commonly used score of renal rejection (7).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the graft leukocyte pattern revealed massive upregulation of nearly all genes of pro-and antiinflammatory cell types analyzed on aTX postoperative day 4 ( (17,18,28,29). Upregulation of these genes (exception: neutrophil granulocytes: CD66, 3.1 6 0.3, P , 0.05) was not detected on aTX postoperative day 1 (meaning that significant graft infiltration had not yet started at that time).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite success of achieving long-term graft survival in murine models using anti-CD154 and tolerance induction in rodent models, it has proven difficult to establish allograft tolerance in larger animals, including nonhuman primates and humans (10,11). One hypothesis is that higher frequencies of memory alloreactive T lymphocytes are present in pretransplanted nonhuman primates and humans, and that these memory T cells have different activation requirements compared with naive cells (12).…”
mentioning
confidence: 99%
“…They present different characteristics which prevent their manipulation in vivo. Indeed, it was shown that memory cells are resistant to depletion (Gallon et al, 2006), costimulatory blockade (Yang et al, 2007) and apoptosis (Wu et al, 2004) and can be activated by low antigenic signal and without costimulation (Cho et al, 2000). A lot of studies thus try to specifically target human memory T cells by neutralizing the tumor necrosis factor which is an important factor for the generation of memory T cells (Croft, 2003;Yuan et al, 2003) or by blocking adhesion molecules, then inhibiting the infiltration of such T cells in the graft (Ellis and Krueger., 2001;Dedrick et al, 2002;Vicenti et al, 2007).…”
Section: The Use Of Monoclonal Antibodies: T Cell Depletion and Blockmentioning
confidence: 99%